Catolicismo popular entre o amor e a cobiça: Inter-relações entre catolicismo popular, igreja católica oficial e poder público em Trindade - Silva, Karine Monteiro da (2005)
The present work aims at to analyze the instituted religious phenomenon in the city of Trindade, express in the love and the covetousness a belief of The Holy Father. Being possible to perceive the performance of the Catholic church, while legitimate official institution, to develop administration methods "to control" this complex, at the same time where it is allied to the social yearning and politicians of the "laypeople" to be able to reach the support that it is necessary. Taking as base the form of administrative perfomance of Public Power, also public politics in agreement with the necessities displayed for practitioners and promoters of the religions manifestations in favor of the development if the city are traced. These two last agents, they structuralize a reception system of power and raise wealth lead from the Popular Catholicism that, in it considers them to observe: until point it presents characteristics of subordination and/or resistance, not being this sufficiently a passive agent but an active in this religious context.